Circular economy in textiles and apparel processing, manufacturing, and design - Muthu, Subramanian Senthilkannan (Textile Institute book series, 2019)
"Circular Economy in Textiles and Apparel: Processing, Manufacturing, and Design explores the progress and potential of circularity for waste reduction across the textiles supply chain and provides guidance in how to implement in practice. The fashion and textiles industries are increasingly turning to the concept of circular economy in order to address environmental issues such as the excessive generation of landfill waste. Circular Economy in Textiles and Apparel: Processing, Manufacturing, and Design is the first book to provide guidance on this subject, presenting the tools for implementing this paradigm and their impact on textile production methods. Sustainable business strategies are covered, as are new design methods that can help in the reduction of wastes and case studies of the circular economy currently in operation in the textiles industry. Drawing on contributions from leading global experts in industry and academia, this book covers every aspects of this increasingly important subjects and speculates on future developments. It will be a valuable guide to practitioners across the textile industry with an interest in sustainability, including R&D, manufacturing, and management, as well as academics in the fields of sustainable textiles, materials, and industry."--